(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
This article examines the specific problems faced by students and teachers in the study of Russian literature in educational institutions. It analyzes such aspects as insufficient teacher training, limited curricula, a lack of modern methodological materials, difficulties in perceiving classical texts, low student motivation, the use of outdated teaching methods, lack of time for literature study, technological constraints, and sociocultural differences in foreign-language groups. Possible solutions to these problems are proposed, aimed at improving the effectiveness of the educational process and enhancing the quality of teaching Russian literature